2021
DOI: 10.3390/jcm10173874
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Periodontal Pathogens in Oral Samples and Cardiac Specimens in Patients Undergoing Aortic Valve Replacement: A Pilot Study

Abstract: This observational study aimed to: (i) assess the presence of periodontal disease among patients requiring aortic valve replacement; (ii) investigate the presence of oral pathogens in aortic valve specimens and compare them with the microorganisms detected in the oral cavity. Twenty-six patients (15 men and 11 women) were scheduled to be visited the day before the cardiac surgery: periodontal conditions were accurately registered through clinical and radiographic examinations; dental plaque or salivary samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(65 reference statements)
2
6
0
Order By: Relevance
“…Two different multiplex PCRs were performed to identify the presence of: (a) P. gingivalis , P. intermedia , and A. actinomycetemcomitans [ 39 ], and (b) T. forsythia , T. denticola , and A. naeslundii . Additionally, a single PCR was performed to identify Actinomyces spp., S. mutans , Veillonella spp., and Lactobacillus spp., as previously reported [ 40 ]. PCR reactions were performed using the 5Prime Hot Master Mix (Quantabio, Beverly, MA, USA) according to manufacturer’s instructions.…”
Section: Methodssupporting
confidence: 69%
“…Two different multiplex PCRs were performed to identify the presence of: (a) P. gingivalis , P. intermedia , and A. actinomycetemcomitans [ 39 ], and (b) T. forsythia , T. denticola , and A. naeslundii . Additionally, a single PCR was performed to identify Actinomyces spp., S. mutans , Veillonella spp., and Lactobacillus spp., as previously reported [ 40 ]. PCR reactions were performed using the 5Prime Hot Master Mix (Quantabio, Beverly, MA, USA) according to manufacturer’s instructions.…”
Section: Methodssupporting
confidence: 69%
“…This strengthens the possibility that bacteria found in plaque deposits enter the blood circulation, with Porphyromonas gingivalis and Prevotella pasteri being statically significant. Streptococcus mutans was the most frequent non-periodontal microorganism identified at the valvular level, a species commonly found in other studies [ 59 ].…”
Section: Links Between Dysbiotic Oral Microbiota and Valvular Heart D...supporting
confidence: 53%
“…In another study conducted on patients undergoing aortic valve replacement, Pardo et al [ 59 ] observed the presence of the same oral pathogens in both the aortic valvular samples and the oral cavities of the patients. Seven patients were edentulous, fifteen presented severe to moderate periodontitis, and only four were considered orally healthy.…”
Section: Links Between Dysbiotic Oral Microbiota and Valvular Heart D...mentioning
confidence: 99%
“…First, the above-mentioned bacteria related to periodontitis are anaerobic, showing a complex metabolism and special cultivation requirements [23]. Second, the common potential periodontal pathogens or their DNA were found in different cardiac tissue [24,25]. Furthermore, the causality of such an infection would be hard to prove; therefore, a study on the oral cause of LVAD-related infection would need another design similar to the current study.…”
Section: Discussionmentioning
confidence: 91%